2019
DOI: 10.1016/j.micron.2019.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting electron beam damage in calcite nanoparticles

Abstract: We report electron fluence thresholds for the degradation of calcite nanoparticles under electron irradiation by both conventional and scanning TEM (CTEM and STEM), using time resolved phase contrast imaging and EDX spectroscopy at both 80 kV and 300 kV accelerating voltages. We show that the degradation pathway of calcite involves disruption of the crystal lattice with the evolution of pores and transformation to calcium oxide and carbon dioxide. Depending on irradiation conditions (CTEM or STEM), the calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…As a result, the O 2− anion changes its charge state and is displaced from the Al 2 O 3 lattice. Comparing our data (electron energy 40 keV) with the results of [28], where etching was observed at a higher energy of 100 keV and a duration of 30 min, it can be noted that the cross-section of inelastic electron scattering in a dielectric medium, which causes its radiolysis, decreases with increasing electron energy [38,39]. It can be argued that a decrease in the energy of electrons at energies below 100 keV enhances the processes of radiolysis of the sapphire surface.…”
Section: Effects Of Inelastic Scattering Of Electrons On the Surface ...supporting
confidence: 63%
“…As a result, the O 2− anion changes its charge state and is displaced from the Al 2 O 3 lattice. Comparing our data (electron energy 40 keV) with the results of [28], where etching was observed at a higher energy of 100 keV and a duration of 30 min, it can be noted that the cross-section of inelastic electron scattering in a dielectric medium, which causes its radiolysis, decreases with increasing electron energy [38,39]. It can be argued that a decrease in the energy of electrons at energies below 100 keV enhances the processes of radiolysis of the sapphire surface.…”
Section: Effects Of Inelastic Scattering Of Electrons On the Surface ...supporting
confidence: 63%
“…6 b) but diffraction patterns did not match any known CaCO 3 polymorphs. Beam damage during TEM resulting in calcium carbonate transformation is fairly common 41 , 42 and could be the reason for the inconclusive TEM analysis.
Figure 6 Visualization of a single vaterite precipitate using FIB-SEM and TEM.
…”
Section: Resultsmentioning
confidence: 99%
“…These alternative approaches will yield differing sensitivities to the electron beam (i.e. differing values of the critical electron fluence), because the type and extent of observed damage varies from loss of atomic order, loss of material to changes in chemistry, and each of these will depend on the predominant damage mechanism responsible for these particular changes (22).…”
Section: Damage Of Beam Sensitive Materials By Electronsmentioning
confidence: 99%
“…Alternatively, as shown in figure 5, Hooley et al . [22] compared the radiolytic damage of calcium carbonate nanoparticles (a moderately sensitive, direct-damage inorganic material) by both CTEM and STEM and concluded that hydrocarbon contamination induced by the focused STEM probe was important in mitigating damage, as has been noted by others [7072]. The build-up of hydrocarbon contamination may protect the specimen in two ways: by improving the conduction of electrons, thus reducing the extent of radiolysis or electrostatic charging by suppressing charge build-up in a similar manner to intentionally deposited carbon coatings [68]; or by preventing the migration of molecular fragments and facilitating their recombination, meaning that there may be some structural damage without significant chemical change [73].…”
Section: Low Dose Stem Versus Ctemmentioning
confidence: 99%
See 1 more Smart Citation